Corporate governance rating in a small open capital market: Methodology and applications in the Greek market - Spanos, L.; Tsipouri, L.; Xanthakis, M (IUP Journal of Corporate Governance, 2006)
The need of institutional investors to evaluate the Corporate Governance (CG) practices of listed companies resulted in many attempts to construct the CG rating methodologies. This paper, in response to this situation, attempts to quantify the compliance of large capitalization Greek companies with international best practices. The methodology consists of a questionnaire reflecting the Greek CG code, which basically replicates the OECD principles. Other wellregarded CG codes are also taken into account. Then, a rating system based on CG indicators is constructed and applied for the years 2001 and 2003. The total rating results for the years 2001 and 2003 demonstrate a relatively satisfactory improvement. The highest compliance is in the category of shareholder rights, while weak compliance appears in the last category, which incorporates commitment to CG, CSR and the relations with shareholders. The exercise, using practically all agreed principles of the OECD, could demonstrate a reasonable degree of compliance of the average company rated. Its limitation in that respect is that it could not satisfy investigations on convergence. The indicators used are highly pertinent to measure compliance but not convergence, which is not within the initial targets and needs a longer time series analysis. The methodology is applied in a small open economy and may have significant implications in other similar capital markets. Methodologically, the merit of the exercise lies in its approach toward the creation of "collectively subjective" weightings, and is valuable to institutional investors, policymakers, regulators and academics. The upgrading of the Greeek capital market to a mature market status and the global competition for capital has boosted the CG debate in Greece. In addition, the recent corporate failures and financial scams around the world have increased awareness that proper CG is fundamental to the efficient operation of capital markets. The need of institutional investors to evaluate the CG practices of the listed companies resulted in many attempts to construct CG rating methodologies. This paper presents an attempt to quantify the compliance of large capitalization Greek companies with international best practices. Firstly, the literature on CG ratings is reviewed. Secondly, a brief history of the CG in Greece is presented. Then, the structure of our CG rating methodology and the results are described. Finally, the findings and proceedings with some critical points are summarized.